Answer:
This question is very big, you should shorten your question a bit so that I can answer it quickly, the rest is just that I did not understand the question a bit
Answer:
Each friend got 2 apples
Step-by-step explanation:
[original amount of apples]-[Apples Sally has after distribution] = [friends] x [number of apples]
Filling in the brackets, you get this equation.
15-9=3 x apples per friend
6=3 x apples per friend
2 = apples per friend
Answer:
![Log_41024=5](https://tex.z-dn.net/?f=Log_41024%3D5)
Step-by-step explanation:
The change of form formula (exponential to logarithm) is:
![a^x=b\\Log_ab=x](https://tex.z-dn.net/?f=a%5Ex%3Db%5C%5CLog_ab%3Dx)
Looking at the problem given, we can simply write the logarithmic form as:
![4^5=1024\\Log_41024=5](https://tex.z-dn.net/?f=4%5E5%3D1024%5C%5CLog_41024%3D5)
This is the answer.
Let
rA--------> radius of the circle A
rB-------> radius of the circle B
LA------> <span>the length of the intercepted arc for circle A
</span>LB------> the length of the intercepted arc for circle B
we have that
rA/rB=2/3--------> rB/rA=3/2
LA=(3/4)<span>π
</span>
we know that
if <span>Both circle A and circle B have a central angle , the ratio of the radius of circle A to the radius of circle B is equals to the ratio of the length of circle A to the length of circle B
</span>rA/rB=LA/LB--------> LB=LA*rB/rA-----> [(3/4)π*3/2]----> 9/8π
the answer is
the length of the intercepted arc for circle B is 9/8π
Answer:
B
Step-by-step explanation:
![m+4\leq6](https://tex.z-dn.net/?f=m%2B4%5Cleq6)
We subtract 4 from each side to get ![m\leq2](https://tex.z-dn.net/?f=m%5Cleq2)
Let's plug in a random point such as 0.
![0+4\leq6 \\ \\ 4\leq6](https://tex.z-dn.net/?f=0%2B4%5Cleq6%20%5C%5C%20%5C%5C%204%5Cleq6)
Since this is true, the inequality we made is true.